Special education teachers' experienced burnout and perceived fit with the professional community: A 5‐year follow‐up study. (10th April 2019) - Soini, T.; Pietarinen, J.; Pyhältö, K.; Haverinen, K.; Jindal‐Snape, D.; Kontu, E.
Abstract : In many countries, including in Finland, promoting inclusive school practices supporting pupils' equal rights for learning is the focus of school development. Special education teachers play a central intermediary role in developing inclusive school and classroom practices by providing support both for pupils and peer teachers. This may increase their risk of experiencing exhaustion, cynicism towards the teacher community and/or inadequacy in pupil–teacher relationships. However, the resources of a school's social working environment experienced as a functional teacher–working environment fit may buffer the risk of developing burnout. This study aims to gain a better understanding of the interrelation between, and development of, special education teachers' experienced burnout symptoms and perceived teacher–working environment fit across time. The longitudinal study included two measurements (in year 2010, n  = 760 and in year 2016, n  = 485). The results show that special education teachers' experienced inadequacy in pupil–teacher relationships predicted teacher exhaustion, cynicism towards the teacher community and inadequacy in pupil–teacher relationships 5 years later. Moreover, a perceived good teacher–working environment fit predicted lower cynicism towards the teacher community 5 years later.